THE EFFECT OF SUSTAINED SILENT READING ON STUDENTS READING COMPREHENSION OF EIGHTH GRADE STUDENTS AT SMP NEGERI 1 SUKASADA - ., I Komang Piska Sandya Nata; ., Prof. Dr. Anak Agung Istri Ngr. Marhaeni; ., Luh Diah Surya Adnyani, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2017)
Tujuan dari penelitian ini adalah untuk menemukan ada atau tidaknya pengaruh dari penerapan Sustained Silent Reading pada pemahaman membaca siswa. Penelitian ini adalah penelitian quasi-experimental yang menggunakan desain post-test only control group. Populasi dalam penelitian ini adalah semua siswa kelas delapan di SMP Negeri 1 Sukasada, sedangkan sampel pada penelitian ini adalah 57 siswa yang terdiri dari 28 siswa dari kelas VIII E sebagai kelompok eksperimen dan 29 siswa dari kelas VIII F sebagai kelompok kontrol. Sampel dikelompokan dengan menggunakan random sampling on the intact group. Pengumpulan data dilakukan melalui post-test dalam bentuk pilihan ganda. Data yang diperoleh dianalisis secara deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa skor rata-rata untuk kelompok eksperimen (79.00) lebih tinggi daripada skor rata-rata untuk kelompok kontrol 75,65. Selanjutnya, analisis statistik inferensial melalui uji t-test mengungkapkan bahwa tobs lebih tinggi dari tcv yaitu 2,225> 2,008 (ɑ = 0,05). Selanjutnya hipotesa melalui uji t-test mengungkapkan jika ada pengaruh dari Sustained Silent Reading terhadap pemahaman membaca siswa dengan hasil effect size sedang 0.58 (t=2.225, df=55, p < .05¬). Kata Kunci : Sustained Silent Reading, Pemahaman Membaca, Whole Language Approach. The purpose of this study was to discover whether or not there is an effect of the implementation of Sustained Silent Reading toward students’ reading comprehension. This study was quasi-experimental study with post-test only control group design. The population of this study was all eighth grade students in SMP Negeri 1 Sukasada, while the sample of this study was 57 students consisting of 28 students from VIII E as experimental group and 29 students from VIII F as control group. The sample was gathered by using random sampling technique on the intact groups. The data were collected through post-test in form of multiple choice test. The obtained data were analysed descriptively and inferentially. The result of this shows that mean score for experimental group (79.00) is higher than the mean score for control group (75.65). Furthermore, inferential statistical analysis through independent sample test revealed that tobs is higher than tcv which is 2.225 > 2.008 (ɑ = 0,05¬). Moreover the hypothesis through independent sample test revealed that there is an effect of Sustained Silent Reading toward students’ reading comprehension with the moderate effect size 0.58 (t=2.225, df=55, p < .05¬)keyword : Sustained Silent Reading, Reading Comprehension, Whole Language Approach.